Using a technology-organization-environment framework to investigate the factors influencing e-business information technology capabilities. (November 2015) - Yeh, Chi-Hung; Lee, Gwo-Guang; Pai, Jung-Chi
One key focus of the business community is determining how to combine information technology capability (IT capability) with business strategies. However, most of these studies have been based on a conceptual framework or researched the performance of e-businesses from a strictly technological point of view. This study sought to identify the factors that influence e-business IT capability using a technology-organization-environment framework. The subjects of this study were IT department heads in 1, 000 large companies in Taiwan. Structural equation modeling was used to verify the validity of the research hypotheses. Results show that the key factors influencing e-business IT capability are as follows: IT maturity, IT infrastructure, IT human resources, support from top management, partnership quality, and competitive pressure. IT capability significantly affects the implementation of IT strategies. The results of this study could serve as important reference data for companies seeking to develop IT capability in the expansion of e-business.